La condonación de obligaciones tributarias a grandes grupos económicos y su incidencia en la crisis presupuestaria del país. - Medina Paccha, Dayanna Lizbeth (2021)
The present thesis entitled: "The remission of tax obligations to large economic groups and its impact on the country's budget crisis" is the result of a thorough research on the legal figure of remission in the tax field. In Ecuador several tax remission processes have been granted, the most notable being the one granted in 2018, which is the object of this research, because it was aimed at benefiting large economic groups, which made evident the power that the wealthiest sectors of the country possess, a power that transcends the economic to the political sphere and which was used to obtain the total remission of their interests, fines and surcharges. Within the present work of investigation it is tried to present which was the affectation that the process of condonation of year 2018, granted by means of the Law for the Productive Promotion, Attraction of Investments, Generation of Employment Stability and Fiscal Equilibrium, caused in the general budget of the State, For this purpose, it was necessary to carry out a comparative economic analysis of the annual proforma for tax income approved by the National Assembly with the net national collection obtained by the Internal Revenue Service (SRI), Fines and surcharges were affected to the general budget of the State, since the tax collection of periods prior to the 2018 remission process was not the estimated one, which caused the executive to have to make adjustments in the budget prioritizing needs and stopping making works or services planned in the years of non collection, It is for this reason that the Tax Administration should have collected the tax debt in its entirety and not only the capital, so that the defaulting taxpayers would have received a penalty for their conduct and the money obtained could have covered, to a large extent, the budget deficit, which in the last ten years has been consecutive. Furthermore, within the present investigation, it will be possible to corroborate that by granting a tax remission process for the benefit of the 15 wealthiest sectors of the country, compliance with constitutional tax principles is not being guaranteed, especially that of equality and equity, since at the time this process was granted, privileged treatment was given to the taxpayers who were beneficiaries of the remission, and furthermore, congratulations were given and negligence in collection was allowed, thus favoring the unfulfilled taxpayers, It is for this reason that the remission processes must be extraordinary events, granted in strictly necessary cases, since the government must issue regulations aimed at achieving the sufficiency of the tax system and not the opposite, since the collection capacity must be increased and the efficiency of the tax administration improved, in order to positively influence both national production and tax collection statistics. Finally, the integration of the conceptual, doctrinal and legal framework; as well as the use of several research methods such as inductive, deductive, historical, comparative, among others, and the field work carried out were of great help within the development of the present research, since all this allowed me to establish a legal proposal of reform aimed at establishing in the Tax Code certain parameters of obligatory compliance so that a process of remission can be granted, this with the purpose of giving solution to this problem that affects negatively the economy of the Ecuadorian State.